TINJAUAN MENGENAI KONSEP MARITIME SAFETY BELT INDONESIA DALAM UPAYA PERLINDUNGAN WILAYAH NEGARA KESATUAN REPUBLIK INDONESIA - Febrika Ganang Adista (BELLI AC PACIS, 2015)
This research examines the concept of Maritime Safety Belt Indonesia expressed by the National Authority for State Border Management (BNPP) in an effort to protect territorial integrity Republic of Indonesia. This research is the normative nature of legal research peskriptif. Secondary data types include primary, secondary law materials. Data collection techniques used are using the approach of law and the study of librarianship. The results of this research show that the welfare and security of the development policy in Indonesia must be started from the border regions and the outermost small islands (PPKT) in an effort to protect the region's sovereignty and territorial jurisdiction of the (Maritime Safety Belt) Republic of Indonesia.